Marijuana Use, Recent Marijuana Initiation, and Progression to Marijuana Use Disorder Among Young Male and Female Adolescents Aged 12-14 Living in US Households - Valerie L Forman-Hoffman; Cristie Glasheen; Kathryn R Batts (SAGE Publishing, 2017)
Marijuana initiation during adolescence, and early adolescence in particular, is associated with adverse health consequences. Our study used 2005-2014 data from the annual, cross-sectional National Survey on Drug Use and Health to study the prevalence and correlates of marijuana initiation, use, and marijuana use disorder (MUD; abuse or dependence) among 12- to 14-year olds living in civilian US households (n = 84 954). Examined correlates included age, sex, race/ethnicity, poverty status, metropolitan status, year of survey, depression, tobacco use, alcohol use, and fighting at school. Sex differences in the correlates of lifetime use and past year marijuana initiation were tested via interaction. Lifetime prevalence of marijuana use was 5.5%; 3.2% reported past year initiation. About 1 in 6 (16.8%) past year initiates progressed to MUD within 12 months of first use. Although men had higher prevalence of lifetime use than women, past year initiation did not differ by sex. On examining the sex*race/ethnicity interaction effects, findings determined that non-Hispanic black and Hispanic men had higher prevalence estimates of ever using marijuana and incidence of past year initiation as compared with non-Hispanic white men; these race/ethnicity differences were not found among women. Identifying correlates of initiation and progression to MUD among young adolescents is critical to improve prevention and treatment program targets.